2021
DOI: 10.1186/s12885-021-08727-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors associated with Pneumocystis jirovecii infection in patients with solid tumors: study of thirteen-year medical records of a large cancer center

Abstract: Background Pneumocystis jirovecii pneumonia (PCP)-related risk factors among patients with solid tumors are not completely defined. Thus, we aimed to characterize PCP cases with underlying solid tumors, to highlight the factors contributing to its development besides the prolonged use of moderate-to-high dose corticosteroids. Methods We retrospectively reviewed the medical records of patients with solid tumors diagnosed with PCP between 2006 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…We calculated the daily steroid dose equivalent as prednisolone (PSL) per patient for 3 months before PJP onset to evaluate steroid administration. Only in 34% of patients who received PSL 20 mg or another steroid with an equivalent dose or higher for ≥ 2 weeks, is this rate comparable to that previously reported (30%) [ 3 ]. Therefore, the steroid dosing method was not the only risk factor for PJP in patients with solid tumors.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We calculated the daily steroid dose equivalent as prednisolone (PSL) per patient for 3 months before PJP onset to evaluate steroid administration. Only in 34% of patients who received PSL 20 mg or another steroid with an equivalent dose or higher for ≥ 2 weeks, is this rate comparable to that previously reported (30%) [ 3 ]. Therefore, the steroid dosing method was not the only risk factor for PJP in patients with solid tumors.…”
Section: Discussionsupporting
confidence: 70%
“…In a previous study, CD+ T-cell counts in immunosuppressed persons with or without HIV infection could be indicative of high PCP risk [ 2 , 11 ]. This study finding could be additional evidence that CD4+ T-cell and total lymphocyte count monitoring may be required in patients with solid tumors [ 3 , 12 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Treatment with moderate-dose to high-dose corticosteroid has long been regarded a significant risk factor for P. jirovecii infection. Observational studies have demonstrated that daily glucocorticoid doses exceeding 20–30 mg of prednisolone equivalents and in particular those longer than 4–8 weeks’ duration are associated with PJP 7 22–27. Some patients on corticosteroid doses equivalent to as little as 16 mg of prednisolone daily and those on intermittent non-daily regimens of less than 4 weeks’ duration have also been shown to develop PJP 7 28.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the clinicopathological characteristics of lung cancer patients diagnosed with PCP were chemoradiotherapy treatment, metastatic lung cancer, prior steroid treatment, and HIV infection [ 3 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%